Lipid Mediators in Critically Ill Patients: A Step Towards Precision Medicine - Cioccari, Luca; Luethi, Nora; Masoodi, Mojgan (Frontiers in Immunology, 2020)
A dysregulated response to systemic inflammation is a common pathophysiological feature of most conditions encountered in the intensive care unit. Recent evidence indicates that a dysregulated inflammatory response is involved in the pathogenesis of various ICU-related disorders associated with high mortality, including sepsis, acute respiratory distress syndrome, cerebral and myocardial ischemia, and acute kidney injury. Moreover, persistent or non-resolving inflammation may lead to the syndrome of persistent critical illness, characterized by acquired immunosuppression, catabolism and poor long-term functional outcomes. Despite decades of research, management of many disorders in the ICU is mostly supportive, and current therapeutic strategies often do not take into account the heterogeneity of the patient population, underlying chronic conditions, nor the individual state of the immune response. Fatty acid-derived lipid mediators are recognized as key players in the generation and resolution of inflammation, and their signature provides specific information on patients’ inflammatory status and immune response. Lipidomics is recognized as a powerful tool to assess lipid metabolism and the interaction between metabolic changes and the immune system via profiling lipid mediators in clinical studies. Within the concept of precision medicine, characterizing the individual immune response may allow for better stratification of critically ill patients as well as identification of diagnostic and prognostic biomarkers. In this review, we provide an overview of the role of fatty acid-derived lipid mediators as endogenous regulators of the inflammatory response and future directions for use of clinical lipidomics to identify lipid mediators as diagnostic and prognostic markers in critical illness.